Phytophthora Infestations in Forest Ecosystems - Scanu, Bruno; Jung, Thomas (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The oomycete genus Phytophthora represents one of the most notorious groups of tree pathogens in natural and semi-natural forest ecosystems. Since the discovery in the 1960s of the invasive P. cinnamomi, threatening some of the world's richest plant communities in Australia, numerous Phytophthora diseases have been reported on forest trees worldwide, which were previously unknown to science. The most notable examples include the oak and beech declines triggered by different Phytophthora spp. in Europe and North America, the findings of sudden oak death and sudden larch death caused by P. ramorum in the Western USA and the U.K., respectively, and the association of P. austrocedri with mal del ciprés in Argentina and juniper decline in the U.K. All these epidemic events are driven by exotic invasive Phytophthora species, introduced through infested nursery plants from their native overseas environments. In recent years, many independent surveys have studied the diversity of Phytophthora species and the diseases they are causing across a diverse range of forests and other natural ecosystems. This Special Issue presents papers on Phytophthora surveys performed in different biogeographic regions and addresses the pathways, and ecological and economic impacts of these invasive forest pathogens.